PEMBUKTIAN UNSUR PERSAMAAN PADA POKOKNYA DAN ITIKAD TIDAK BAIK DALAM UPAYA PEMBATALAN MEREK TERDAFTAR - Arnold Arnold; Marni Emmy Mustofa; Basuki Basuki (SINERGI : Jurnal Riset Ilmiah, 2026)
Legal protection for trademarks in Indonesia still faces problems with trademark registration in bad faith that have substantial similarity with other parties' marks. The fundamental problem lies in the absence of clear objective parameters for determining the criteria of substantial similarity and bad faith, creating legal uncertainty in trademark cancellation efforts. This research examines two issues: first, what are the criteria for proving substantial similarity and bad faith in trademark cancellation cases; second, what is the ideal regulatory concept for proving these elements to strengthen legal certainty. The research employs theories of evidence, legal protection, and legal certainty and justice to analyze Supreme Court Decision Number 123 K/Pdt.Sus-HKI/2023 regarding the cancellation of "Cap Segi Tiga Intan + Logo" trademark. This research uses normative legal methods with statutory, conceptual, and case approaches. Secondary data consists of primary legal materials such as legislation and court decisions, secondary legal materials including books and scientific journals, and tertiary legal materials. Data collection through library research and analyzed qualitatively using systematic interpretation. The findings indicate that criteria for proving substantial similarity are conducted through three approaches: analysis of dominant elements, examination of overall mark impression, and evaluation of consumer confusion likelihood. Proving bad faith requires concrete evidence of unauthorized use of another party's product identity, chronological relationship of mark usage, and deliberate similarity. Normative gaps exist in the absence of objective parameters for examining these elements. The ideal regulatory concept includes six pillars: revision of Article 21 Elucidation of Trademark Law, issuance of Ministerial Regulation on substantive examination methods, issuance of Supreme Court Regulation on trademark dispute guidelines, enhancement of DGIP preventive function through technology and notification systems, establishment of alternative dispute resolution mechanisms, and harmonization with international standards. The research recommends that lawmakers revise evidentiary provisions, the Supreme Court issue examination guidelines, and DGIP improve substantive examination accuracy.